Probing Questions In English Classroom: A Study Of Teaching Practice (Praktik Keterampilan Mengajar) English Department Students Year 2016 - Selvia Gumay (UICELL, 2018)
Abstract Probing question as part of basic teaching skills becomes a substantial aspect in teaching learning activities to dig up students’ higher order thinking. This study aimed to investigate the types of probing questions used by English Department practice teachers year 2016 of State University of Jakarta. This study implemented qualitative research which focused on classroom observation. Data of this study were probing question utterances asked by practicesd teacher during teaching learning process. The instrument of this study was classroom observational sheet. The data source of this study were 3 English Department PKM students and students of 3 class in SMP Negeri 97 and SMP Negeri 139. The result of the study is in average all types of probing questions found in three English Department PKM students, however only 1 student employed all types of probing question and prompting probing question is the most frequent used by the practice teachers. The study also showed that probing question used in delivering material section in English teaching-learning process. The study also showed that the students were able to respond probing questions used by practice teacher by think correctly and critically while the teacher probed them with probing questions. Keywords: Probing Question, Students’ higher order thinking, English classroom, Teaching practice.